Device and method for preparing feed for promoting intestinal health of vespa mandarinia - HUANG XIANGJU; CHEN JIKUAN; PENG GUO; HUANG GUOZHONG (2023)
The invention discloses a preparation device and method of a feed for promoting intestinal health of vespa mandarinia, and the device comprises a box body which is provided with a box door; the number of the sliding plates is two, the two sliding plates slide on the two sides of the inner wall of the box body respectively, a screening frame is detachably installed between the two sliding plates, and a shaking assembly used for shaking the sliding plates up and down is installed on the box body; the feeding hole is formed in the top of the box body; the dust-proof assembly is installed on the box body and used for sucking dust in the box body, the dust-proof assembly comprises a concentration frame fixedly inserted into one side of the box body, and a collection box is fixedly installed on one side of the box body. Dust generated in the screening process can be sucked through the dustproof assembly, the situation that the dust drifts to the external environment to pollute the environment and is sucked by worke